Report of the Expert Group to Develop Concrete Proposals for Restructuring the Centrally Sponsored Schemes (CSS) - Planning Commission (Planning Commission, 2006)
The Expert Group Report on Restructuring Centrally Sponsored Schemes (CSS), chaired by Shri Arvind Varma, presents a comprehensive framework to enhance the efficiency, accountability, and effectiveness of CSS in India. Recognizing challenges such as overlapping objectives, weak fund tracking, and limited state-level ownership, the report proposes several reforms. Key recommendations include the introduction of zero-based budgeting every five years, establishing a minimum financial threshold of ₹300 crore for new CSS, and implementing sunset clauses to ensure schemes have defined outcomes and timelines. The report emphasizes state autonomy in selecting schemes relevant to local needs, involving Panchayati Raj Institutions (PRIs) in planning and execution, and aligning CSS with Millennium Development Goals (MDGs). An Incentive Fund of ₹5,000 crore is proposed to reward states performing effectively against MDG targets. To address deficiencies in financial management, the report highlights the need for standardized expenditure classification, computerized accounting systems, utilization certificates backed by vouchers, and comprehensive audit trails with independent verification. Funds are recommended to flow through state budgets to enhance transparency and accountability.
Government of India Planning Commission New Delhi September, 2006
Government of India Planning Commission New Delhi September, 2006
Keywords: Centrally Sponsored Schemes (CSS); Planning Commission; Restructuring; Zero-Based Budgeting; State Autonomy; Panchayati Raj Institutions; Monitoring and Evaluation; Millennium Development Goals (MDGs); Incentive Fund; Accountability; Fund Tracking; Expenditure Certification; Audit Trail; India; Governance Reform